Pengaruh Return on Assets, Free Cash Flow, Debt to Equity Ratio, Pertumbuhan Penjualan Terhadap Kebijakan Dividen Pada Perusahaan Property and Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2014-2016 - Hantono Hantono; Ike Rukmana Sari; Felicya Felicya; Miria Daeli (Politeknik Ganesha Medan, 2019)
The purpose of this research is to examinethe effect of the return on assets, free cash flow, debt to equity ratio, sales growth to dividen policy on property and real estate companies in Indonesia Stock Exchange in the period 2014-2016. The population in this research are property and real estate companies listed in Indonesia Stock Exchange active from 2014 to 2016 with a sample of 18 companies. Based on analysis, it can be concluded that free cash flow positive and significant effect on dividen policy. Return on assets, debt to equity ratio and sales growth does not effect on dividen policy.